Beneficial protective effect of pramipexole on light-induced retinal damage in mice. (October 2015) - Shibagaki, Keiichi; Okamoto, Kazuyoshi; Katsuta, Osamu; Nakamura, Masatsugu
Abstract: We investigated the effects of pramipexole, a potent dopamine receptor D2/D3 agonist, on light-induced retinal damage in mice, H2 O2 -induced retinal pigment epithelium ARPE-19 cell injury in humans, and hydroxyl radical scavenging activity in a cell-free system. Pramipexole (0.1 and 1 mg/kg body weight) was orally administered to mice 1 h before light exposure (5000 lux, 2 h). Electrophysiological and morphologic studies were performed to evaluate the effects of the pramipexole on light-induced retinal damage in mice. Pramipexole significantly prevented the reduction of the a- and b-wave electroretinogram (ERG) amplitudes caused by light exposure in a dose-dependent manner. In parallel, damage to the inner and outer segments (IS/OS) of the photoreceptors, loss of photoreceptor nuclei, and the number of Tdt-mediated dUTP nick-end labeling (TUNEL)-positive cells in the outer nuclear layer (ONL) caused by light exposure were notably ameliorated by pramipexole. Additionally, pramipexole suppressed H2 O2 -induced ARPE-19 cell death in vitro in a concentration-dependent manner. The effect of pramipexole was significant at concentrations of 10 −6 M or higher. Pramipexole also significantly prevented H2 O2 -induced activation of caspases-3/7 and the intracellular accumulation of reactive oxygen species (ROS) in a concentration-dependent manner ranging from 10 −5 to 10 −3 M. Furthermore, pramipexole increased the scavenging activity toward a hydroxyl radical generated from H2 O2 in a Fenton reaction. Our results suggest that pramipexole protects against light-induced retinal damage as an antioxidant and that it may be a novel and effective therapy for retinal degenerative disorders, such as dry age-related macular degeneration. Highlights: Pramipexole protected against light-induced retinal damage in mice. Pramipexole inhibited H2 O2 -induced ARPE-19 cell death. Pramipexole prevented H2 O2 -induced activation of caspases-3/7 in ARPE-19 cells. Pramipexole decreased H2 O2 -induced accumulation of reactive oxygen species (ROS) in ARPE-19 cells. Pramipexole directly scavenged ROS.